An interaction language for argumentation-based negotiation - Rueda, Sonia Vivian (2005)
Language is the medium used by heterogeneous and autonomous members of a community to communicate and to exchange knowledge. Social work allows members in a community to resolve problems that they could not face individually, but they must be able to interact in order to do it. Furthermore, is necessary to have a negotiation mechanism that allows members of a system to interact through it, trying to reach an agreement in order to satisfy their goals. Our work is oriented towards the design of an interaction language that allows argumentation-based negotiation among collaborative BDI agents.